Evaluation of the diagnostic utility of leucocyte in comparison to other biomarkers in the management of patients with pulmonary tuberculosis - Ibeh, Nancy C.; Ibekie, Adaora G.; Amilo, Grace I.; Manafa, Patrick C.; Chukwuanukwu, Rebecca O. (International Journal of Research in Medical Sciences, 2020)
Background: Pulmonary tuberculosis (PTB) is an infectious and debilitating disease that affects millions of people each year. Simple, reliable and cost effective biomarkers are vital to fore-stall the morbidity and mortality that is hallmark of the infection especially in resource poor economy. Methods: This comparative study enlisted 140 subjects: 80 had PTB and 60 do not. Blood of 8mls was collected; 3mls in K2-EDTA for FBC testing with XE-2100 Sysmex and ESR by Westergreen method. The remainder was used for serum CRP assay by ELISA. The radiological extent was determined from Chest X ray report and disease severity using modified Bandim TB scoring was extracted from the case note. The aim of the study is to investigate the relationship and diagnostic utility between leucocyte with CRP, ESR, radiological extent of disease and disease severity in PTB. Results: Mean Lymphocyte count was lower while TWBC, Neutrophil and Monocyte counts were higher in subjects compared to control (p<0.05). Median CRP, ESR, NLR, NMR and MLR were higher in subjects compared to control (p<0.05), NLR and MLR showed strong positive significant correlation with ESR, disease severity, and radiological extend of disease. NMR (p= 0.00) had a negative correlation with ESR (p<0.05) and inverse correlation with disease severity and radiological extent. Conclusions: This study found NLR, MLR and NMR as a readily, easily available and inexpensive indices that are as efficient and comparable to known biomarkers in PTB infection, therefore could serve as valuable predictive biomarker in areas of high disease burden with weak economy.